2011
DOI: 10.1021/jz201224x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling C–H Abstraction Reactivity of Nonheme Fe(IV)O Oxidants with Alkanes: What Role Do Counter Ions Play?

Abstract: b S Supporting Information T here is a surge of interest in synthetic models of mononuclear nonheme iron enzymes, 1À6 which perform CÀH activation and lead to the formation of alcohols and alkenes. Both the enzymes 1 and the synthetic models utilize high-valent iron-(IV)-oxo complexes as the active species. 2À5 One of the potent synthetic complexes is [N4PyFe IV O] 2+ (N4Py: N,N-bis (2-pyridylmethyl)-bis(2-pyridyl) methylamine), which is depicted in Scheme 1 and which is capable of activating even cyclohexane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 53 publications
(190 reference statements)
8
105
0
Order By: Relevance
“…For equatorial donors an increase of the donor strength of the ligand will lower the redox potential of the Fe IV O moiety and increase the pK a of the Fe III OH product formed upon hydrogen-atom transfer. It has been found that ligand donor moieties in cis-position to the oxo unit (equatorial donors) exert less influence on the reactivity of Fe IV O (S = 1) octahedral complexes as compared to those ligated trans (axial) 48 as "trans-ligands can interact with both σ-and π-orbitals involved in the FeO bond but cis-ligands cannot". 53 However, in the present case, the effect of replacing equatorial pyridyl donors with (Nmethyl)benzimidazolyl units is quite significant.…”
Section: ■ Discussionmentioning
confidence: 99%
“…For equatorial donors an increase of the donor strength of the ligand will lower the redox potential of the Fe IV O moiety and increase the pK a of the Fe III OH product formed upon hydrogen-atom transfer. It has been found that ligand donor moieties in cis-position to the oxo unit (equatorial donors) exert less influence on the reactivity of Fe IV O (S = 1) octahedral complexes as compared to those ligated trans (axial) 48 as "trans-ligands can interact with both σ-and π-orbitals involved in the FeO bond but cis-ligands cannot". 53 However, in the present case, the effect of replacing equatorial pyridyl donors with (Nmethyl)benzimidazolyl units is quite significant.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The dipositive charge of 4 was neutralized using two perchlorate anions (ClO 4 ) − . 28 The counter ions were positioned as found in the crystal structures of 1 , 3 17d and 4 . 29 During geometry optimization and throughout the reaction path, the position of the counter ions essentially remained constant.…”
Section: Methodsmentioning
confidence: 99%
“…24,28 Spin densities and natural bond order (NBO) charges of the optimized structures at B2+Solv level (Table S14–S19) were also analyzed for the identification of the electronic states of stationary points.…”
Section: Methodsmentioning
confidence: 99%
“…The recently reported explicit use of counter-ions in the non-heme iron catalyst reaction mechanism suggests that it helps to avoid the irregularities associated with self-interaction problem inherent in DFT. [37][38][39] Hence, we have also used SbF6 ─ ions along with all intermediates and transition states (after extensive site sampling) to get rid of the charge inconsistency associated with the reaction steps as well as to account for the effect of non-bonding interactions induced by the counter ions in the reaction environment.…”
Section: Methodsmentioning
confidence: 99%